Hubungan Gaya Mengajar Guru dengan Motivasi Belajar Peserta Didik pada Mata Pelajaran Sejarah Kebudayaan Islam - Siti Rukmini Nugrahaeni; Asis Saefuddin; Alvin Yanuar Rahman (STIT Fatahillah, 2024)
This research began with observations in Class IV in the History of Islamic Culture subject, where it was found that the teacher's voice was difficult to hear, the teacher often left the classroom to chat and often played with gadgets during the lesson. This causes students to lose motivation. This research aims to determine teachers' teaching styles and students' learning motivation and the relationship between the two. Teaching style indicators include voice variations, the concentration of attention, silence, gaze contact, body movements, teaching positions, behavior, and habits. Indicators of learning motivation include the desire to succeed, encouragement in learning, hopes and aspirations, appreciation for learning, interesting activities, and a conducive learning environment. The research hypothesis is that there is a significant relationship between teaching style and learning motivation. The research method uses a quantitative approach with correlation techniques, observation, questionnaires, and documentation. Questionnaires were distributed to 61 respondents in Class IV-A and IV-B. Data analysis techniques include normality, homogeneity, linearity, and correlation tests, with validity and reliability tested first. The research results show that the data is normally distributed, homogeneous, and linear. The teacher's teaching style and student learning motivation are both in the perfect category. The relationship between teacher teaching style and student learning motivation shows a positive result of 0.333, although in the low category